2018
DOI: 10.1021/acs.inorgchem.8b01386
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Two-Stage Oxidation of Sulfide by Chlorine Dioxide

Abstract: The sulfide-chlorine dioxide reaction was found to have two distinct kinetic stages at alkaline conditions. The first stage proceeds so rapidly that it can only be measured by a stopped-flow technique at low temperature and leads to the parallel formation of polysulfide and sulfate as sulfur-containing products. At the same time, chlorite, chlorate, and chloride are produced from chlorine dioxide in detectable amounts, suggesting a complex stoichiometry. A nine-step kinetic model including short-lived intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…An interesting mechanistic feature may be highlighted in the case of a reaction between hydrogen sulfide and chlorine dioxide [55]. This reaction can be divided into two separate kinetic stages.…”
Section: Thiourea Oxides As the Sources Of Sosmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting mechanistic feature may be highlighted in the case of a reaction between hydrogen sulfide and chlorine dioxide [55]. This reaction can be divided into two separate kinetic stages.…”
Section: Thiourea Oxides As the Sources Of Sosmentioning
confidence: 99%
“…It is shown that these reactions start with electron transfer from the substrate to chlorine dioxide and with oxygen transfer from chlorine dioxide to the substrate, simultaneously. Authors [55] have shown, however, that analogous initiation step HS − + ● ClO 2 ⇌ ● HS + ClO 2 − does not proceed. Instead of this, the fast formation of the weak adduct ● HSClO 2 − is observed: HS − + ● ClO 2 ⇌ ● HSClO 2 − The next step is accompanied by formation of sulfide radical and chlorite: ● HSClO 2 − + OH − → ● S − + ClO 2 − + H 2 O A parallel decomposition of ● HSClO 2 − produces chlorine radical and sulfoxylate: ● HSClO 2 − → SO 2 H − + ● Cl…”
Section: Thiourea Oxides As the Sources Of Sosmentioning
confidence: 99%
“…However, this approach usually takes a few days, not to mention the significant increase in operation costs. Conventional chemical sulfide oxidation employs ClO 2 or Fenton’s reagents [ 10 , 11 ]. The former technology requires additional equipment for the generation of ClO 2 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional chemical sulfide oxidation employs ClO 2 or Fenton’s reagents [ 10 , 11 ]. The former technology requires additional equipment for the generation of ClO 2 [ 10 ]. The latter requires acidic conditions and generates a considerable amount of ferric sludge [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Essa explosão respiratória é capaz de estimular, a ação de eferocitose dos macrófagos, levando a resolução da inflamação aguda(LUO et al, 2016). Evento este, que acreditamos ter ocorrido de forma acentuada no grupo tratado deste estudo, decorrente da maior atividade da MPO comparado ao controle, culminado em um maior estímulo para a transição da fase inflamatória para a fase proliferativa da cicatrização.Além disso, em feridas, a MPO atuou recrutando fibroblastos e estimulando a síntese de colágenos, o que faz com que ela tenha um papel fundamental na biossíntese da MEC, favorecendo desta forma o reparo tecidual(DENICHILO et al, 2015).O aumento significativo da MPO no grupo tratado com relação ao controle aos 3 dias, se deve a possível capacidade de oxidação do sulfeto de hidrogênio pelo dióxido de cloro a 150 ppm(CSEKÖ et al, 2018). Segundo Pálinkás e colaboradores (2015), a mieloperoxidase pode ser inibida na presença do sulfeto de hidrogênio.…”
unclassified